Ethnobotanical study on the valorization of a rare forest, fruit and medicinal plant (Prunus avium) in north-western Tunisia - Nouri, Jdaidi; Selmi, Houcine; El Baher Dhafer, Cyrine; Abbes, Chaabane (Ethnobotany Research and Applications, 2025)
Background: This ethnobotanical study aimed to promote the rare medicinal plant Prunus avium from Jendouba region in northwestern Tunisia and to collect general information regarding its therapeutic applications. Methods: Ethnobotanical surveys were conducted among rural populations and herbalists in the three areas (Tabarka, Ain Draham, and Ghardimaou) using a questionnaire on Prunus avium. Following the conclusion of the fieldwork, the collected information was processed. It was then sorted and structured into a matrix using XLSTAT software, which enabled the creation of graphs and tables. Results: The data collected shows that Prunus avium, also known as wild cherry, is widely used in the region. In fact, the research conducted in these three areas showed that it was mainly recommended for its anti-inflammatory (23%), diuretic (20.9%), sleep-promoting (16.1%), relief from osteoarthritis (15%), and cholesterol-lowering properties (15%). Respondents also indicated that the leaves and fruits were the most commonly used parts, with 68% and 32%, respectively. Also, decoction (25.55%), fruit juice (23.53%), infusion (21.87%), and compress (20.65%) were generally mentioned. Conclusion: This work serves as a valuable source of information for pharmacological research, providing a foundation for evaluating the therapeutic efficacy of Prunus avium. It emphasizes the effective transmission of knowledge regarding the applications and beneficial effects of wild cherries from one generation to the next. Keywords: Prunus avium, ethnobotanical survey, method of preparation, therapeutic uses, northwestern Tunisia.